1976
DOI: 10.1302/0301-620x.58b1.1270486
|View full text |Cite
|
Sign up to set email alerts
|

Protection from stress in bone and its effects. Experiments with stainless steel and plastic plates in dogs

Abstract: Modulus of tensile strength Fatigue limit elasticity =UTS as percentage (MN/rn2) (MN/m') of UTS 3 16 stainless steel .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(85 citation statements)
references
References 10 publications
3
77
1
Order By: Relevance
“…A rigid immobilization protects bone from normal loading, and numerous reports have been given that show cancellous transformation and weakening of existing cortical bone after plate osteosynthesis (Tonino et al 1976, Woo et al 1976and Paavolainen et al 1978. It is probable that the same principle applies to new bone in the 34' process of osteogenesis, stress protection giving a slow rate of healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rigid immobilization protects bone from normal loading, and numerous reports have been given that show cancellous transformation and weakening of existing cortical bone after plate osteosynthesis (Tonino et al 1976, Woo et al 1976and Paavolainen et al 1978. It is probable that the same principle applies to new bone in the 34' process of osteogenesis, stress protection giving a slow rate of healing.…”
Section: Discussionmentioning
confidence: 99%
“…That instability gives increased production of external callus is considered an established fact. The mechanical properties of callus are, however, a matter of disagreement, as an increasing number of authors seem to find that "a certain amount" of external callus promotes earlier functional bridging of the fracture gap (Uhthoff & Dubuc 1971, Tonino et al 1976and Sudmann 1976. Kiintscher (1950) states from clinical experience that "good stability" gives "better" healing.…”
mentioning
confidence: 99%
“…Adequate post-operative immobilization was ensured in all cases. plastic failure occur due to minor loads in small plates and secondary major trauma in large plates [5]. The most common failure of plate is fatigue failure.…”
Section: Methodsmentioning
confidence: 99%
“…Stress protection of various types of osteosynthesis in diaphyseal bones has been described (Tonino et al 1976, LAftman et al 1980). Terjesen and Benum (1983b, c) showed that the degree was dependent on the type and the duration of fixation.…”
Section: Per Adolphson' Ulf Jonsson' Nils Dalen' and Anders Ehrnberg'mentioning
confidence: 99%